Usability evaluation of a telecommunications mobile application - Cubillo-Mora , Jose (2024)
This article was based on research conducted through a set of measures established to evaluate the usability of a mobile application developed by a telecommunications company in Costa Rica. The application, which has the function of managing services and performing postpaid, prepaid and home services, as well as making online purchases, was subjected to evaluation with the participation of 10 users with different levels of digital experience. In the evaluation process, the ISO 25062, ISO 9241.11 and SUS (System Usability Scale) standards were applied. The ISO standards provided guidelines for evaluating the usability of software products, focusing on the user's efficiency and effectiveness in using the tool. On the other hand, the SUS scale made it possible to measure the usability perceived by users, considering ease of use, complexity and overall user satisfaction. The results of the research indicated that, in general terms, the design of the application was adequate. However, areas of improvement were identified that could be implemented to enhance the user experience. These improvements were suggested based on the design issues identified during the research.